Land. 2 - Yamashita, Kazumi, 1959- (Yen Press, 2026)
Although An did somehow manage to pull off a second great escape with her aunt Mari this time, the cruelty of the world broke Mari's spirit. With her father dead, and her aunt despondent, An has no choice but to face the reality that every misfortune that has befallen her family was caused by her getting too close to The Beyond. But as she's trying to forget everything about that place, who should appear but Kazune, who claims a "weapon" that connects her world and The Beyond...